2022
DOI: 10.3390/diagnostics12040803
|View full text |Cite
|
Sign up to set email alerts
|

Early Markers in Resistant Schizophrenia: Effect of the First Antipsychotic Drug

Abstract: Background: Schizophrenia is a mental illness with a multifactorial etiology and clinical presentation. Treatment is mainly with antipsychotic drugs. Despite the increasing number of antipsychotic drugs, there has been no significant change in the percentage of resistant cases. These data gave us reason to look for a link between the effect of the first individually selected antipsychotic drug and the established resistance to therapy. Method: An assessment has been made of 105 patients with chronic schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…In the meta-regression analyses, there were significant associations between higher TRS prevalence, older age (0.0066, p = 0.0436), 7 , 25 - 31 , 33 - 38 , 40 , 42 - 47 , 49 - 51 , 53 , 55 , 56 , 58 - 61 , 65 - 68 , 70 higher percentage of clozapine users (0.0056, p = 0.0003), 25 , 30 , 31 , 33 , 34 , 38 , 39 , 41 , 43 , 45 , 46 , 50 , 54 , 56 , 59 - 61 , 64 - 68 lower Global Assessment of Functioning score (-0.0260, p = 0.0324), 45 , 55 , 60 , 61 and lower total TRRIP score (-0.0143, p = 0.0059), 7 , 8 , 16 , 25 - 71 as well as three specific TRRIP criteria: less fulfillment of current symptom severity threshold (-0.0641, p = 0.00462), 7 , 8 , 16 , 25 - 71 less fulfillment of minimum functional impairment (-0.0439, p = 0.0376), 7 , 8 , 16 , 25 - 71 and time course (-0.0634, p = 0.0326) 7 , 8 , 16 , 25 - 71 ( ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the meta-regression analyses, there were significant associations between higher TRS prevalence, older age (0.0066, p = 0.0436), 7 , 25 - 31 , 33 - 38 , 40 , 42 - 47 , 49 - 51 , 53 , 55 , 56 , 58 - 61 , 65 - 68 , 70 higher percentage of clozapine users (0.0056, p = 0.0003), 25 , 30 , 31 , 33 , 34 , 38 , 39 , 41 , 43 , 45 , 46 , 50 , 54 , 56 , 59 - 61 , 64 - 68 lower Global Assessment of Functioning score (-0.0260, p = 0.0324), 45 , 55 , 60 , 61 and lower total TRRIP score (-0.0143, p = 0.0059), 7 , 8 , 16 , 25 - 71 as well as three specific TRRIP criteria: less fulfillment of current symptom severity threshold (-0.0641, p = 0.00462), 7 , 8 , 16 , 25 - 71 less fulfillment of minimum functional impairment (-0.0439, p = 0.0376), 7 , 8 , 16 , 25 - 71 and time course (-0.0634, p = 0.0326) 7 , 8 , 16 , 25 - 71 ( ).…”
Section: Resultsmentioning
confidence: 95%
“…Studies that only included patients with FES found a lower TRS prevalence (22%, 95%CI 18.4-25.8; n = 10,579) 16 , 25 , 27 , 38 , 39 , 62 , 64 , 66 , 69 than those that only included multi-episode patients (39.5%, 95%CI 32.2-57.0; n = 4,685) 8 , 29 , 31 , 34 , 36 , 40 , 43 , 49 , 70 (Q = 17.7, p < 0.0001).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The first line of treatment is the use of typical and atypical antipsychotics, but when this approach fails, clozapine is the last resort for treatment-resistant schizophrenia (TRS) [ 1 ]. It was suggested that failure of the first typical or atypical antipsychotic already justifies switching to clozapine [ 2 ] There is strong evidence that the immune system and neuroinflammation play a central role in the pathophysiology of SCZ [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Epidemiological studies have demonstrated that various infections and autoimmune disorders in the prenatal period or in early childhood, as well as chronic stress and genetic susceptibility, are associated with increased risk of developing SCZ later in life.…”
Section: Introductionmentioning
confidence: 99%
“…A special place among the clinical predictors of therapeutic resistance is occupied by psychopathic disorders with auto aggressive tendencies, traditionally considered within the framework of heboid states. At the same time, until recently, the main drug from the group of neuroleptics used to overcome resistance was clozapine [8,9,10,11,12,13]. In practice, up to 30% of patients remain intact to its action, which dictates the need for combination therapy [14,15,16].…”
mentioning
confidence: 99%